Enhanced production of lipase from ‘NC Mutant’ moulds for transesterification reactions - Mubarik, Nisa Rachmania; Siswodarsono, Trismilah; Nabilasani, Galih Cendana (Penerbit Universiti Kebangsaan Malaysia, 2025)
Lipase can be used for biodiesel production, specifically in transesterification reactions. Nut C (NC) is a fungal isolate derived from palm kernels and palm kernel waste, capable of producing lipase. The objective of this study was to obtain a mutant mould with higher transesterification activity compared to its wild type counterpart (NC). The mutation process on NC mould was carried out using ultraviolet (UV) radiation followed by ethyl methane sulfonate (EMS). UV-induced mutation on NC produced four isolates, with m4.3NC1 exhibiting higher transesterification activity than the wild type, with an increment of 138.8% (from 0.121 U/mg to 0.168 U/mg). Subsequent EMS mutations of the mutant m4.3NC1 isolate, designated as m5.4NC, increased the transesterification activity from 0.168 U/mg to 2.048 U/mg (1119% increment as compared to the wild type). Molecular identification of the NC isolate showed 100% similarity with the Aspergillus fumigatus CMXY15837 strain. The highest specific enzyme activity of the NC mutant was observed at pH 6 and a temperature of 50 °C. This study showed that the mutation of NC mould using UV, followed by EMS, significantly enhanced its transesterification activity.